The enduring echoes of juvenile bullying: the role of self-esteem and loneliness in the relationship between bullying and social media addiction across generations X, Y, Z - Lissitsa, Sabina; Kagan, Maya (Frontiers in Psychology, 2024)
Objective Being bullied is a profoundly distressing experience for children and adolescents, with the potential for adverse mental and behavioral outcomes throughout their adult years. This study aims to explore the association between juvenile bullying, self-esteem, loneliness, and social media addiction among men across three generational cohorts: X, Y, and Z. Method The study utilized an online survey, administering structured questionnaires to 797 men aged 18–58 divided into three generational cohorts: 142 individuals from Gen X (born between 1965 and 1980), 275 from Gen Y (born between 1981 and 1996), and 380 from Gen Z (born between 1997 and 2005). Results The findings demonstrate that across all three generations, there was a positive correlation between experiencing bullying in one’s youth and social media addiction in adulthood. Among Gen X, self-esteem did not act as a mediator in this relationship, nor did loneliness moderate the links between bullying and social media addiction, or between self-esteem and social media addiction. However, for Gen Y and Z, self-esteem was found to mediate the relationship between bullying and social media addiction. Loneliness moderated the association between self-esteem and social media addiction in Gen Y and the association between bullying and social media addiction in Gen Z. Conclusion The differences observed among generational cohorts can be attributed to changes in masculinity norms, the evolution of bullying types, and the rapid development of social media platforms, catering to the distinct needs and gratifications of each generation.